2019
DOI: 10.1071/an17855
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics and fatty acid composition of the meat of lambs fed cassava silage and dry tamarind (Tamarindus indica)

Abstract: The objective of the present study was to determine the effect of the addition of dry tamarind (Tamarindus indica L.) residue to cassava (Manihot esculenta, Crantz) silage on the carcass traits, quality and fatty acid profile of lamb meat. Forty 6-month-old (±2 days) castrated lambs (crossbred Santa Ines × mixed breed) with initial bodyweights of 22.1 ± 3.0 kg were used in a completely randomised design with four treatments (0, 100, 200 or 300 g/kg of DM of dry tamarind residue) and 10 replicates (animals). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…The ∑SFA, ∑MUFA, and ∑PUFA meat concentrations were not affected by the increasing PKO concentrations in the bull diets. PUFAs are considered beneficial to consumer health [ 41 ], emphasizing ∑ n − 3, as their consumption reduces the risk of cardiovascular disease [ 42 ]. The ∑ n − 6: ∑ n − 3 ratio (2-3:1) observed in this study agrees with the ratio reviewed and described by Zárate et al [ 43 ], in which ∑ n – 6: ∑ n − 3 ratio values of 2-4:1 were associated with reduced risks of breast, prostate, colon, and kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The ∑SFA, ∑MUFA, and ∑PUFA meat concentrations were not affected by the increasing PKO concentrations in the bull diets. PUFAs are considered beneficial to consumer health [ 41 ], emphasizing ∑ n − 3, as their consumption reduces the risk of cardiovascular disease [ 42 ]. The ∑ n − 6: ∑ n − 3 ratio (2-3:1) observed in this study agrees with the ratio reviewed and described by Zárate et al [ 43 ], in which ∑ n – 6: ∑ n − 3 ratio values of 2-4:1 were associated with reduced risks of breast, prostate, colon, and kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Essas características permitem o cultivo da mandioca em áreas em que muitas culturas não podem ser cultivadas (Santos et al, 2018). Em regiões onde se tem potencial de produção de mandioca (Zambom et al, 2014), a utilização desta para a alimentação animal torna-se uma alternativa real, que contribui para a redução dos custos dos componentes das dietas (Napasirth et al, 2015).…”
Section: Introductionunclassified
“…Mistakenly, the general FA profile is associated with an increase in the incidence of cardiovascular diseases and atherosclerosis which somewhat is likely to affect consumer perception of meat products (Parodi, 2016; Ribeiro et al ., 2018). Concomitantly, there has been a growing interest in finding appropriate and natural ways to positively manipulate the FA composition of red meat in order to minimize the risks to human health (Wood et al ., 2008; Parodi, 2016; Gesteira et al ., 2018; dos Santos et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Diets with high energy density, as is the case of high concentrate diets, improve animal performance and promote greater deposition of fat, which can in turn cause a variation in the meat composition (Santos-Silva et al ., 2002; Araújo et al ., 2017). However, several studies have demonstrated that by increasing the amounts of concentrate in finishing diets, the proportion of saturated fatty acids (SFA) in the meat also increases (dos Santos et al ., 2019), which is not a desirable trait for health-concerned consumers. In contrast, other studies have shown that higher levels of roughage in ruminant diets promote increased deposition of Σ n–3 polyunsaturated fatty acids (PUFA) in the muscle due to higher levels of linolenic acid (C18:3) found in forages (Realini et al ., 2004; Wood et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%